2020
DOI: 10.1002/lary.29146
|View full text |Cite
|
Sign up to set email alerts
|

Curbing the Cough: Multimodal Treatments for Neurogenic Cough: A Systematic Review and Meta‐Analysis

Abstract: Objectives/Hypothesis Neurogenic cough affects 11% of Americans and causes significant detriment to quality of life. With the advent of novel therapies, the objective of this review is to determine how procedural therapies (e.g., superior laryngeal nerve block) compare to other established pharmacologic and non‐pharmacologic treatments for neurogenic cough. Methods With the assistance of a medical librarian, a systematic review was performed using PICOS (patients, interventions, comparator, outcome, study desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 72 publications
0
13
1
Order By: Relevance
“…6,13 The most well-established non-pharmacologic treatment for neurogenic cough includes cough suppressive therapy with a speech and language pathologist. This therapy has been shown to improve patient cough-related quality of life, 15,16 but these interventions are often limited by cost, patient access to a therapist, and necessity of regular visits. 6,7 A recently emerging therapy that may be a more convenient option for patients is SLN block with local anesthetic and long-acting corticosteroid.…”
Section: Introductionmentioning
confidence: 99%
“…6,13 The most well-established non-pharmacologic treatment for neurogenic cough includes cough suppressive therapy with a speech and language pathologist. This therapy has been shown to improve patient cough-related quality of life, 15,16 but these interventions are often limited by cost, patient access to a therapist, and necessity of regular visits. 6,7 A recently emerging therapy that may be a more convenient option for patients is SLN block with local anesthetic and long-acting corticosteroid.…”
Section: Introductionmentioning
confidence: 99%
“…CPAP did improve cough in those with OSA, possibly by its impact on lung inflation or on gastro-esophageal reflux ( 23 , 26 , 27 ), however, its use in other chronic respiratory diseases is unexplored. A recent systematic review explored multimodal treatments for refractory chronic cough and concluded that medical therapy, SLP, and procedural therapy all improve outcomes of chronic cough ( 9 ). In this review, all study designs were included and SLP was described as including a large number of interventions, such as physiotherapy and behavioral therapy and no distinction between them was performed, which could have influenced the conclusions presented ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review explored multimodal treatments for refractory chronic cough and concluded that medical therapy, SLP, and procedural therapy all improve outcomes of chronic cough ( 9 ). In this review, all study designs were included and SLP was described as including a large number of interventions, such as physiotherapy and behavioral therapy and no distinction between them was performed, which could have influenced the conclusions presented ( 9 ). Our review compliments these results, by presenting the data from people with chronic respiratory diseases, including only the highest evidence available (RCTs) and differentiating between different disciplines and techniques performed for people with refractory chronic cough.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations